Density and seasonal dynamics of Bemisia tabaci and its predators in different agricultural landscapes in South China - Li, Ming-Jiang; Yang, Shao-Wu; Chen, Guo-Hua; Dou, Wen-Jun; Shang, Hao-Pei; Zhang, Xiao-Ming (Frontiers in Plant Science, 2022)
Bemisia tabaci is the main pest of agriculture in many regions of the world. The resistance of whitefly in pesticides has increased as a consequence of the continuous irrational use of wide-spectrum pesticides. Thus, pesticides are no longer always effective as a long-term control method. The agricultural landscape can affect the occurrence of an insect population. The objective of this study was to clarify the occurrence of whitefly and its predators in tomato fields in different agricultural landscapes. Different landscapes are classified into urban, flower, water, and mountain landscapes by the principal component analysis method. In 2018-2019, whitefly had the longest main activity period and the lowest density in the flower landscape. The water landscape helped to maintain the highest densities of whitefly during the main activity period. Nine species of predators were sampled, and Nesidiocoris tenuis, Chrysoperla sinica, Menochilus sexmaculata, and Harmonia axyridis were the dominant species throughout the sampling season in both years. During the main activity period, N. tenuis had the highest density in all sampled landscapes. The density of the dominant predators was the highest in the flower landscape, and each natural predator had the largest temporal niche width in the 2-year sampling period. Bemisia tabaci, N. tenuis, and M. sexmaculata were highly synchronized temporally. The flower landscape showed satisfactory results in suppressing whitefly. Increasing the proportion of flowering plants and increasing the diversity of plant crops in the agricultural landscape can effectively reduce the densities of whitefly during an outbreak.